The effects of added niacin during lactation on sow and litter performance - Robert D. Goodband; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1987)
An on-farm field study utilizing 231 sows was conducted to determine the effects of added niacin during a 21-day lactation on sow and litter performance. At farrowing, sows were assigned to one of two dietary treatments that provided either 200 or 1000 mg niacin/day. All Iitters were equalized within dietary treatment by 24 hours following farrowing. All sows had a similar number of pigs born alive, pigs equalized per litter, and average pig and litter birth weights. Feeding sows a diet providing 1000 mg additional niacin did not significantly affect the number of pigs weaned, pig survival, or average pig and litter weaning weights. Furthermore, added niacin did not affect sow feed intake as measured on a daily basis or for the overall lactation. However, those sows fed 1000 mg additional niacin lost slightly more weight (P<.15) during lactation than those fed the control diet.; Swine Day, Manhattan, KS, November 19, 1987
Keywords: Swine day; 1987; Kansas Agricultural Experiment Station contribution; no. 88-125-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 528; Swine; Niacin; Lactation; Performance